Employees' awareness of their impact on corporate reputation - Helm, Sabrina (Journal of business research, 2011)
Corporate reputation is critical for cultivating stakeholder relationships and, specifically, for regaining public trust. Corporate reputation results from the firm's interactions with stakeholders, emphasizing the important role employees play in reputation management. However, employees are not necessarily aware of, or prepared for, this extra-role assignment, indicating a gap in research and a managerial challenge. The purpose of the present article is to identify how employees' awareness of their impact on their employers' reputation is influenced by pride, job satisfaction, affective commitment, and perceived corporate reputation. An online survey of employees working for firms ranked in Fortune's America's Most Admired Companies Index provides empirical evidence. The findings underline the prominent effect pride in membership has regarding employees' awareness of their impact on corporate reputation. Study findings further deliver insights into opportunities and risks for managers who wish to use internal reputation building strategies to enhance corporate reputation.